Environmental, social, governance risk versus cooperation models between financial institutions and businesses. Sectoral approach and ESG risk analysis - Zioło, Magdalena; Bąk, Iwona; Cheba, Katarzyna; Filipiak, Beata Zofia; Spoz, Anna (Frontiers in Environmental Science, 2023)
Introduction: ESG risk and the business sector are essential in the process of adapting business models towards sustainability. The article aims to analyze ESG risk, taking into account these business sectors that are most affected by ESG risk, and to identify the relationship between ESG risk and cooperation models of financial institutions and companies (Anglo-Saxon/German-Japanese). The original research approach was based on including the financial system model in the analysis of ESG risk impact and the companies’ methods of achieving sustainable business models with external funding. Methods: The study is based on a two-stage analysis. First, fuzzy cognitive maps are used to evaluate the strength and direction of the relations between factors included in the companies’ sustainable business models according to the business sectors. At the second stage, a correspondence analysis was carried out to distinguish four groups of companies’ industries characterized by homogenous features related to the business sector, sustainable business model (SBM), and the way to transform to sustainability. Results: Methods of achieving sustainability in companies’ business models differ depending on business sectors. The “financial institution—company” cooperation model and recommendations were proposed. Discussion: Financial institutions play a crucial role in financing the transition into sustainable business models. However, their impact differs depending on the business sector and the model of the financial system (bank or market oriented). The study assumes that the financial system model determines the form of cooperation between financial institutions and companies in the process of financing costs towards sustainability.